A high‐performance transition‐metal phosphide electrocatalyst for converting solar energy into hydrogen at 19.6% STH efficiency. Issue 1 (9th June 2022) - Zhang, Hua; Aierke, Abuduwayiti; Zhou, Yingtang; Ni, Zitao; Feng, Ligang; Chen, Anran; Wågberg, Thomas; Hu, Guangzhi
Abstract: The construction of high‐efficiency and low‐cost non‐noble metal bifunctional electrocatalysts for water electrolysis is crucial for commercial large‐scale application of hydrogen energy. Here, we report a novel strategy with erbium‐doped NiCoP nanowire arrays in situ grown on conductive nickel foam (Er‐NiCoP/NF). Significantly, the developed electrode shows exceptional bifunctional catalytic activity, which only requires overpotentials of 46 and 225 mV to afford a current density of 10 mA cm −2 for the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER), respectively. Density functional theory calculations reveal that the appropriate Er incorporation into the NiCoP lattice can significantly modulate the electronic structure with the d‐band centers of Ni and Co atoms by shifting to lower energies with respect to the Fermi level, and optimize the Gibbs free energies of HER/OER intermediates, thereby accelerating water‐splitting kinetics. When assembled as a solar‐driven overall water‐splitting electrolyzer, the as‐prepared electrode shows a high and stable solar‐to‐hydrogen efficiency of 19.6%, indicating its potential for practical storage of intermittent energy. Abstract : A novel strategy is reported with Erbium‐doped NiCoP nanowire arrays in situ grown on conductive nickel foam (Er‐NiCoP/NF). The developed electrode shows outstanding bifunctional catalytic activity for both hydrogen evolution reaction and oxygen evolution reaction. When assembled as a solar‐driven overall water‐splitting electrolyzer, the as‐prepared electrode shows a high and stable solar‐to‐hydrogen efficiency of 19.6%, indicating its potential for practical storage of intermittent energy.